Phenomenological Approach to Imagination In Poetry: Exploring the Creative Role of Imagination in Poetry through a Phenomenological Approach (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Phenomenological studies examine imagination as a dimension of language and explore the creative role of imagination in the creation of new meanings in language. This exploration has many implications in poetry where language is used creatively and new meanings emerge from the creative and unexpected use of language by the poet. This paper aims to  describe  a  phenomenological  account  of  imagination  in   poetry by introducing the concepts that appear most relevant to imagination in poetry within the domain of phenomenological studies. In order to do this, the study focuses on the main tenets  of  phenomenological  studies relevant to  imagination  in poetry, namely the concepts  of ‘metaphor’  and  ‘intentionality’. The  discussion highlights  the level  of creativity of imagination in poetry in comparison with the reduction of imagining to perceiving in language. Likewise, the poetic image in  poetry is also introduced as animage which is not a resume of the old meanings of perception.  Phenomenology of imagination in poeticcreationtakes us beyond the pervious analyses of the characteristics of imagination as a creative faculty and helps to establish a link between creativity, meaning and imagination.